2016
DOI: 10.22260/isarc2016/0055
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing BIM Adoption in Small and Medium Sized Construction Organizations

Abstract: -The advantages and disadvantages of Building Information Modelling adoption have been extensively investigated in available literature. However, the focus of previous studies has been placed mainly on BIM adoption in relatively large organizations and little effort has been made to investigate the effects that the size of the organizations may have on the BIM adoption process and its associated costs and benefits. This study aims to identify factors that affect the BIM adoption process in small and medium siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…Fox 2014), and others have begun to explore the perspectives of smaller firms (Poirier et al 2015;Hong et al 2016), there is a need for more critical perspectives on BIM to counterbalance the claims around industry-wide integration that have become so attached to the technology and the practices it promotes. As part of this, there is an acute need to explore BIM from the perspective of less powerful and influential actors in the industry -the small and medium-sized enterprises (SMEs) that account for the vast majority of firms operating in the sector (Hong et al 2016). Such a perspective contributes towards an emerging perspective on BIM which sees firm context as an important mediator in its implementation and adoption (Poirier et al 2015).…”
Section: It Seemingly Doesn't Really Matter What the Problem Is -Thmentioning
confidence: 99%
“…Fox 2014), and others have begun to explore the perspectives of smaller firms (Poirier et al 2015;Hong et al 2016), there is a need for more critical perspectives on BIM to counterbalance the claims around industry-wide integration that have become so attached to the technology and the practices it promotes. As part of this, there is an acute need to explore BIM from the perspective of less powerful and influential actors in the industry -the small and medium-sized enterprises (SMEs) that account for the vast majority of firms operating in the sector (Hong et al 2016). Such a perspective contributes towards an emerging perspective on BIM which sees firm context as an important mediator in its implementation and adoption (Poirier et al 2015).…”
Section: It Seemingly Doesn't Really Matter What the Problem Is -Thmentioning
confidence: 99%
“…However, how those descriptive studies inform the BIM policies toward SMEs in their countries is not clear. Those barriers before BIM at SMEs were identified by many (Michaloski and Costa 2010;Arayici et al 2011aArayici et al , 2011bKu and Taiebat 2011;Gledson et al 2012;Hong et al 2016;Hosseini et al 2016;Monozam et al 2016;Lam et al 2017) and include the following: (i) cost and time constraints, (ii) lack of experienced and skilled personnel, (iii) overall understanding of BIM, (iv) lack of data on return on investment of BIM and its perceived usefulness, (v) others' capability to collaborate, (vi) software related issues (e.g., interoperability, maintenance, operation ease), (vii) procurement, contract, and standards related issues (e.g., model ownership, intellectual rights, finding optimum procurement arrangements), and (viii) management commitment and (or) leadership.…”
Section: Smes and Bimmentioning
confidence: 99%
“…Hence, to clear this issue, solutions have to be created by researchers, vendors and professional organizations together so that the use of BIM will increase in the Malaysian construction industry (Latiffi, Mohd, & Rakiman, 2015c). Hong, et al (2016) reported that it is hard to adopt new information technology (IT) in the industry due to technical reasons. Problems such as the lack of support system, difficulty to understand the complex softwares and also the low number of skilled technical experts are among the reasons (Latiffi et.…”
Section: Managementmentioning
confidence: 99%